ANALISIS PENGARUH LINGKUNGAN KERJA DAN KEDISIPLINAN KERJA TERHADAP KINERJA KARYAWAN KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH (KSPPS) BAYTUL IKHTIAR PAMIJAHAN KABUPATEN BOGOR DI MASA PANDEMI COVID-19 - Wiguna, Sindiwati; Suryani, Ermi; Putra, Bayu Purnama (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
In Indonesia, the number of cases of the Covid-19 virus in 2019 increased but decreased in 2021. One of the impacts of the Covid-19 pandemic is on the financial sector, such as Sharia Cooperatives. The problems that existed at KSPPS Baytul Ikhtiar Pamijahan during the Covid-19 period were problems with the work environment and work discipline. The purpose of this study was to determine the effect of the work environment and work discipline on employee performance during the Covid-19 period. Data was collected by distributing questionnaires and taking samples using a saturated sampling technique with a total sample of 15 people. The results showed that the work environment had a positive and significant effect on employee performance with a sig value of 0.002 less than 0.05, while work discipline at a significance level of 5% had no significant effect on employee performance with a sig value of 0.737 greater than 0.05. And the work environment and work discipline together have a positive and significant impact on the performance of KSPPS Baytul Ikhtiar employees during the Covid-19 period, with a sig value of 0.000 less than 0.05.